Industrial disputes : essays in the sociology of industrial relations - Eldridge, J. E. T. (London : Routledge & K. Paul ; New York : Humanities P., 1968)
Professor Eldridge summarizes the contents of his book by the following statement: "It will be evident that the chapters of this book focus on a number of issues and themes prominent in the public debates surrounding British industrial relations. These include the causes of strikes, demarcation disputes, the handling of redundancy questions, the effects of technical change on management-worker relations, the role of plant bargaining and the effectiveness of established procedures in regulating industrial relations in specified contexts". dealing with intraindustry strike behavior in depth. One of the primary uses of this book would be a supplement to a course in industrial sociology or sociology of occupations
Includes bibliographical references: p. 264-268.
rpm 22/03/2018
Loans
Keywords: Industrial relations; Strikes and lockouts